Blepharochalasis. Issue 8 (August 1979) - Collin, J R; Beard, C; Stern, W H; Schoengarth, D
Abstract : The condition of blepharochalasis and its treatment are discussed. Four cases are presented which show a physical sign that may help in its diagnosis.